INTELEKTUAL DAN PERANANNYA DALAM MEMBERANTAS KORUPSI DI INDONESIA - Rosmawiah Rosmawiah (MORALITY: Jurnal Ilmu Hukum, 2019)
Indonesia is a country rich in natural resources. The superiority of this natural wealth should be able to bring Indonesia into a developed country. However, in reality there are still many distorted phenomena that are obstacles to the progress of the nation, one of which is corruption. There are still many cases of corruption that occur to this day resulting in the depletion of Indonesia's natural resources without creating prosperity in subsequent generations. Corruption that is increasingly out of control shows that Indonesia's financial accountability has not been implemented well. The question then is, why are there still many unethical phenomena that occur in the prophetic realm? Does intellectual have an important role in preventing and eradicating corruption cases that often occur in Indonesia?